EFEK LAMA PERKECAMBAHAN TERHADAP SIFAT SENSORI DAN KADAR PROTEIN TERLARUT SUSU KECAMBAH KACANG MERAH (Sukarah) UNTUK REMAJA OBESITAS - Nurjanati, Milla; Winarsi, Hery (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
This study aims to determine the effect of germination on the nature of sensory and dissolved protein content of red bean sprouts milk. This non-factorial experimental study used a randomized block design. The factors studied were germination time: 0 hours, 8 hours, 16 hours, and 24 hours. Parameters tested were soluble protein content and sensory properties including color, flavor, taste, and viscosity. Sensory test using hedonic test and hedonic quality with 50 panelist. The results were analyzed using Friedman test followed by Multiple Comparison Test at 5% level, if there is significantly different. Effectiveness index were used to determine the best product. Data were analyzed using F test at 95% confidence level. If there is significantly different continue with DMRT at 5% level.  The results was no effects of the length of time germination on soluble protein content, preferences on color, odor, and viscosity (p> 0.05). The germination period had an effect on hedonic quality in the color, flavor, taste, and thickness of product (p <0,05). The best sprout milk was for 16 hours. Thus, germination affect taste preferences, and hedonic quality in the color, flavor, taste, and viscosity of sukarah.